Assessing Genetic Variability in Taramira (Eruca sativa Mill.) Germplasm for Enhanced Breeding Strategies - Singh, Sukhjot; Ram, Manohar; Gupta, Deepak; Meena, Manoj Kumar; Nayak, Pravat Kumar; Choudhary, Komal; Rahul; Kumar, Rajneesh; Chouhan, Shambhu (International Journal of Economic Plants, 2024)
The present research was carried out to estimate the genetic variability for 13 characters among 30 different germplasm of Taramira (Eruca sativa Mill.) in a randomized block design with three replications over four artificially created environments through different dates of sowing (timely sown 17 Oct. and late sown 5 Nov.) with (Orobanche free and Orobanche infested field) i.e. timely sown, Orobanche free (E1 ), timely sown, Orobanche infested (E2 ), late sown, Orobanche free (E3 ), late sown, Orobanche infested (E4 ) at Research farm of SKN College of Agriculture, Jobner (SKNAU, Jobner) during the rabi 2022–23. Pooled Anova revealed significant differences among germplasm, environments and G×E interaction significant for all the traits except days to maturity, primary branches per plant, siliqua length (cm). Therefore, analysis of variance is carried out separately for each environment, indicated significant differences among all traits. In all four environments, the PCV>GCV value for all characters. After comparing the mean and range for yield and different yield attributing traits in all four environments, it was found that both were highest in E1 for most of the traits. The high heritability coupled with high genetic advance as percentage of mean for all four environments revealed that characteristics such as height of first branch emergence (cm), seeds per siliqua, 1000-seed weight (g) and seed yield per plant (g) had high value. As a result, they might be under the control of additive gene action. Therefore, selection for these characters will be highly responsive.